PRODUKSI DAN TATANIAGA BERAS DI PROPINSI LAMPUNG - Fitriani Fitriani; Hanung Ismono; Novi Rosanti (University of Jember, 2011)
The objective of this research is investigation the rice production system and distribution chain efficiency in Lampung Province. Respondent sample were taken by purposive and snowball sampling, involved 38 people as farmers and trader in any level. Rice production centre in Pringsewu and Tanggamus Regency, and also Bandar Lampung city as trading centre were choosen as location. Descriptive analysis applied in appraisal the rice production system and distribution chain. The result performed that the rice production in average of years was higher than rice consumption (surplus) in Lampung Province. The rice production system at producent level also performed in good condition. The rice distribution chain tended to inefficient condition because the traders in country level get more benefit than others. The fact that 23,735% rice stock from Lampung distributed to others area such as Bengkulu, Padang, and Riau cause the rice stock in market and society hard to identify and then could be the reason to price instability.Key words: rice production, rice distribution chain, stock